Learning Strategies at SD Muhammadiyah 2 Sidoarjo during the Covid-19 Pandemic - Angelia Firdaus; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to identify SD Muhammadiyah 2 Sidoarjo. In accordance with school history, school conditions and school excellence. Coupled with the covid-19 pandemic, this article also examines the policies at SD Muhammadiyah 2 Sidoarjo in carrying out learning in the midst of the covid-19 pandemic and their handling in overcoming student problems during the covid-19 pandemic. This study uses a qualitative descriptive research method with the method of digging information through interviews with informants. Through this method will create a complex and comprehensive picture, and report a detailed view of information obtained from information sources in the natural environment. Based on the research results, SD Muhammadiyah 2 Sidoarjo is dealing with the Covid-19 pandemic by learning boldly. Bold learning is done through virtual meetings via the Zoom app and the school's web. Learning through Zoom meetings and the web is carried out based on odd-even classes. In addition, some extracurricular activities are also running boldly.